The Cognitive representation of speech - Myers, Terry, 1938-; Laver, John; Anderson, John M. (John Mathieson), 1941- (Advances in psychology (Amsterdam, Netherlands), 1981)
The 32 main papers, taken together, provide a comprehensive review of speech research by scientists who have made leading contributions to our understanding of the topics discussed. The papers are assembled within a coherent, problem-oriented structure.